Bibliometric Analysis of the Effect of Sustainable Agricultural Practices on Farmers' Economic Sustainability - Safruddin, Safruddin; Judijanto, Loso; Harsono, Iwan (Westscience Press, 2024)
In the face of global environmental challenges and the urgent need for sustainable development, agriculture takes center stage as a catalyst for transformative change. This bibliometric analysis explores the extensive body of literature pertaining to the impact of sustainable agricultural practices on the economic sustainability of farmers, offering a comprehensive overview of the existing scholarly landscape. Sustainable agricultural practices encompass a range of environmentally friendly, socially responsible, and economically viable farming methods, from organic farming to integrated pest management. This analysis seeks to identify trends, patterns, and knowledge gaps within this domain, mapping the intellectual structure, highlighting key themes, influential authors, and prominent journals. By systematically examining the literature, it provides valuable insights into the current state of knowledge, emerging research frontiers, and areas warranting further exploration, ultimately contributing to the creation of a more sustainable and economically viable future for farming communities worldwide.